2020
DOI: 10.7759/cureus.10657
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hemolytic Anemia With Acute Myocarditis and Cardiogenic Shock: A Rare Presentation of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) cases are on the rise globally, and mortality- and survival-related data are emerging every day. In addition, upcoming reports are suggestive of increased risk of cardiac ailments in high-risk patients. In the context of cardiac involvement, acute myocarditis has become one of the unexplored areas in COVID-19 patients, which could influence the long-term outcomes. In this report, we present a rare case that warrants further study on the subject due to the paucity of data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The most serious cardiovascular complication of COVID-19 patients is myocarditis, which is most commonly defined as an elevation of hypersensitivity cardiac troponin I (cTnI) above the 99 th percentile of the upper reference limit (34). The onset of acute myocarditis results in ischemia and hypoxia and increases the risk of death if it exceeds the bearing capacity of the body (35,36). In addition, both tachyand brady-arrhythmias are known to occur in COVID-19 patients (37).…”
Section: Cardiovascular Complicationmentioning
confidence: 99%
“…The most serious cardiovascular complication of COVID-19 patients is myocarditis, which is most commonly defined as an elevation of hypersensitivity cardiac troponin I (cTnI) above the 99 th percentile of the upper reference limit (34). The onset of acute myocarditis results in ischemia and hypoxia and increases the risk of death if it exceeds the bearing capacity of the body (35,36). In addition, both tachyand brady-arrhythmias are known to occur in COVID-19 patients (37).…”
Section: Cardiovascular Complicationmentioning
confidence: 99%
“…and is associated with immunodeficiency as well as hyper inflammation, the latter manifesting as a cytokine storm [7]. COVID-19 was earlier thought to be a respiratory disease, but it has affected multiple organs [8][9][10][11]. A study done by Desai et al reported that COVID-19 has caused not only physical distress but also had a negative impact on social, economic, and psychological well-being [12].…”
Section: Sars-cov-2 Is Characterized By Hyper-cytokinemia Which Typimentioning
confidence: 99%
“…As of June 8, 2021, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected 29,762,793 people and caused 383,490 deaths, with a case fatality rate of 1.28% in India, which was 1.60% as of September 22, 2020 [1]. The present coronavirus disease 2019 (COVID- 19) is a worldwide multisystemic disorder with devastating medical and social implications [2][3][4]. While COVID-19 related cutaneous symptoms are becoming more common, their precise incidence is yet to be determined, their pathophysiological processes are still unclear, and the involvement of SARS-CoV-2 in their pathogenesis, whether direct or indirect, is still disputed.…”
Section: Introductionmentioning
confidence: 99%